An Alternate Double–Single Track Proposal for High‐Speed Peripheral Railway Lines. (20th May 2014) - Castillo, Enrique; Gallego, Inmaculada; Sánchez‐Cambronero, Santos; Menéndez, José María; Rivas, Ana; Nogal, María; Grande, Zacarías
Abstract This article presents alternate double–single track (ADST) lines as an alternative to double‐track lines. The idea consists of using single track where the infrastructure is very expensive (tunnels and viaducts) and double track where it is cheaper (smooth orography) combined with small changes in departure times so that trains may cross in the double‐track segments with no reduction in travel times. The solution is shown to be very efficient for traffic demands between 30 and 40 trains per day and the costs are reduced substantially (close to 40%). A linear programming program is given that (1) decides the optimal sequence of single and double tracks and (2) optimizes the timetables for the optimal or other alternative sequences. The Palencia–Santander line is used to illustrate the proposal and some suggestions are given to use the ADST lines in several countries.